Whistleblowing Intentions: A Means to Prevent Fraudulent Practices of Bank Employees in Samarinda City - Yulia Tri Cahyani; Felisitas Defung; Zaki Fakhroni (Budapest International Research and Critics University, 2022)
This study aims to determine the factors that influence whistleblowing intentions as a means of preventing fraud of Bank employees in Samarinda City. Using the concepts of Theory of Planned Behavior (TPB) and Theory of Prosocial Behavior. The research sample in the form of bank employees in Samarinda City amounted to 150 employees by applying the non probability sampling method by accidental sampling. The data collection instrument uses an online questionnaire through a Microsoft form and QR Barcode. Dependent variables are in the form of whistleblowing intentions and independent variables in the form of the level of seriousness of the violation, personal responsibility, and personal cost. Partial Least Square analysis method with the help of SmartPLS software version 3.2.7. Shows the result that the degree of seriousness of the violation, and personal responsibility positively affect the intention of whistleblowing. Meanwhile, the personal cost variable has no effect on whistleblowing intentions.